The development of smart flowerpot based on internet of things and mobile and web application technology - Satien Janpla; Chaiwat Jewpanich; Nisanart Tachpetpaiboon; Waraporn Prongsanthia; Butsirin Jewpanich (Institute of Advanced Engineering and Science, 2022)
Cultivation of ornamental plants in the office is popular among office workers and the general public because it can create a good environment in the area, but the plant growers must pay attention to watering the plants, because it may cause the plant to die. With the advancement of internet of things (IoT) technology, used to control devices wirelessly, this research developed the smart flowerpot system that works through mobile and web applications, using a microcontroller to control the system and connect to users via mobile and web application that can monitor the system, and control the operation both directly and automatically. When soil moisture is reduced to a predetermined value, the system will order the plants to be watered automatically, and when the water level is almost completely reduced, the ultrasonic sensor will send a notification to the mobile application to let the user know, after testing the system, it was found that the smart plant pot can work efficiently and can automatically water the plants.